Enhanced efficacy against cervical carcinomas through polymeric micelles physically incorporating the proteasome inhibitor MG132. Issue 6 (27th April 2016) - Matsumoto, Yoko; Miyamoto, Yuichiro; Cabral, Horacio; Matsumoto, Yu; Nagasaka, Kazunori; Nakagawa, Shunsuke; Yano, Tetsu; Maeda, Daichi; Oda, Katsutoshi; Kawana, Kei; Nishiyama, Nobuhiro; Kataoka, Kazunori; et al.
Abstract : Treatment of recurrent or advanced cervical cancer is still limited, and new therapeutic choices are needed for improving prognosis and quality of life of patients. Because human papilloma virus (HPV) infection is critical in cervical carcinogenesis, with the E6 and E7 oncogenes of HPV degrading tumor suppressor proteins through the ubiquitin proteasome system, the inhibition of the ubiquitin proteasome system appears to be an ideal target to suppress the growth of cervical tumors. Herein, we focused on the ubiquitin proteasome inhibitor MG132 (carbobenzoxy‐Leu‐Leu‐leucinal) as an anticancer agent against cervical cancer cells, and physically incorporated it into micellar nanomedicines for achieving selective delivery to solid tumors and improving its in vivo efficacy. These MG132‐loaded polymeric micelles (MG132/m) showed strong tumor inhibitory in vivo effect against HPV‐positive tumors from HeLa and CaSki cells, and even in HPV‐negative tumors from C33A cells. Repeated injection of MG132/m showed no significant toxicity to mice under analysis by weight change or histopathology. Moreover, the tumors treated with MG132/m showed higher levels of tumor suppressing proteins, hScrib and p53, as well as apoptotic degree, than tumors treated with free MG132. This enhanced efficacy of MG132/m was attributed to their prolonged circulation in the bloodstream, which allowed their gradual extravasation and penetration within the tumor tissue, as determined by intravital microscopy. These results support the use of MG132 incorporated into polymeric micelles as a safe and effective therapeutic strategy against cervical tumors. Abstract : We focused on the ubiquitin proteasome inhibitor MG132 as the anticancer agent against cervical cancer cells, and physically incorporated it into micellar nanomedicines for achieving selective delivery to solid tumors and improving its in vivo efficacy. These MG132‐loaded polymeric micelles (MG132/m) showed strong tumor inhibitory in vivo effect against HPV‐positive tumors from HeLa and CaSki cells, and even in HPV‐negative tumors from C33A cells.